COPPER INFLUENCE ON GERMINATION AND GROWTH OF SUNFLOWER (‟HELIANTHUS ANNUUS”) - BOROŞ, Melania–Nicoleta; MICLE, Valer (Studia Universitatis Babeș-Bolyai Ambientum, 2015)
Heavy metal pollution is an important issue worldwide and one of the technologies that can be sustainable in treating the contamination is phytoremediation. One of the plants that is known to tolerate heavy metals is Helianthus annuus. It can deal with heavy metals like Zn, Pb, Ni, Cr, Cd, Cu, As, Fe. In this study, our aim was to determine the plant's tolerance to copper and to investigate its influence on the germination of seeds and plant growth. The measurements and collection of data were made one week after establishing the seed germination test. We analysed which was the highest concentration of copper that the seeds of sunflower can tolerate and what is the effect at low and high concentrations. For a low concentration of copper, the germination rate was high, while a high concentration was toxic. We compared the root and shoot lengths and the fresh and dry weight of the plants to determine the effect of copper on the plant's development. Our investigation concluded that the highest seed copper tolerance of 90 % was at 1 ppm concentration and it decreased significantly to 16 % at the concentration of 10 ppm. At the highest concentrations, the tolerance was low and the seeds had an abnormal development.